Identifying attributes influencing fresh fruits and vegetables (FFV) purchase a comparative study between night market and hypermarket in Klang Valley, Malaysia - Abdullah, Amin Mahir; Gindi, Abdullahi Auwal; Ismail, Mohd Mansor; Mohd Nawi, Nolila (IJECM, 2016)
Fresh Fruits and vegetables (FFV) retailers of various formats are dynamically influencing customers to patronize at their stores. On the other hand, fresh fruits and vegetables consumers are always evaluating which of these retail formats to choose for FFV purchases. This study employs Stimulus –Organism –Response (S-O-R) model to compare consumer format choice between night market and hypermarket retail formats and to evaluate the impact of demographic factor (income level) of consumers on their choice of retail formats for FFV purchases. Mediation effect of attitude as an organism on relationship between stimulus and response was also evaluated. A consumer’s survey was conducted with 700 respondents from Klang Valley Area, Malaysia. A Structural Equation Modeling (SEM) was used in analyzing the data. Based on the empirical results of night markets and hypermarkets’ retail formats, the models significantly fit the two retail formats and income level is not a moderator on the relationships between stimulus, organism and response for the hypermarket retail formats’ choice models.